Health Awareness Throush Communication Media - العكيلي جهاد كاظم (ALBAHITH ALALAMI, 2015)
Means of communication has a great impact on all fields of awareness including health awareness by increasing the knowledge of community about health and developing their abilities to improve human health and cultural awareness. According to the importance of health awareness for a community to develop their intellectual and physical integrity, the researcher has found that it is essential to know the role of means of communication as a source of information for many students being active and main segments to build their society intellectually, socially and economically. The research has focused on the study of health awareness among students and their health knowledge derived from the means of communication. It is a study about AIDS to sample of students from Baghdad University to know their health programs, subjects and information about this disease via the various means of communication. It also studies the use of students to all means of communication and various programs to follow the health awareness about AIDS, its features and ways to prevent it. The researcher has chosen students in two branches: scientific and humanitarian studies. The researcher has concluded that the students have chosen a specific means of communication that satisfy their desires to get more information. Television and the internet have occupied the first and the second rank being the sources of health information or knowledge. The researcher has found a defect in local channels and local programs by the students to enhance their knowledge of health. It appears that there is no difference between male and female in following up the means of communication and health knowledge including the name, the characteristics and the nature of the disease which is a medium rate for male and female students according to the researcher’s digital measure.